Penerapan Kurikulum Merdeka Terhadap Peningkatan Pengetahuan Siswa SMP Brawijaya Kota Malang - Trianjari, Novita (Universitas Negeri Malang, 2024)
Abstract The purpose of writing articles is to explain and understand the application of the independent curriculum to accountability for increasing student knowledge so that the existence of an independent curriculum can improve increasingly advanced human resources. This research uses qualitative research methods with research locations at SMP Brawijaya Malang and utilizes various sources of information in the form of journals, and articles used to find information about the application of the independent curriculum to accountability for increasing student knowledge. The results of this study explain that the learning process by implementing the independent curriculum at SMP Brawijaya runs well provided by schools and teachers starting from infrastructure, teacher freedom in carrying out the student assessment process, implementing remidial programs, interaction between students and teachers, habituating literacy in SMP Brawijaya, and implementing the learning process with an independent curriculum. This has an impact on increasing the knowledge of students at SMP Brawiyaja Malang City. Through an independent curriculum that is well facilitated by the school, SMP Brawiyaja students have high critical thinking and good social spirit.